Tindakan Kriminalisasi Terhadap Seseorang Dengan Menggunakan Instrumen Undang-Undang ITE - Sagung Laksmi Dewi; I Made Rudy Darmika; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2022)
Criminalization is a change in the value of changing many charges that were previously not criminal and not criminal into acts that are considered cunning and need to be punished. This research aims to find out how to regulate someone who commits an act of criminalization and the legal remedies that must be taken if someone is criminalized. This research is a type of normative and conceptual research on this problem. conceptual, case and comparative. This research emphasizes the interpretation and construction of law to obtain several legal norms, conceptions, lists of regulations and their implementation in concrete cases. From the discussion, the following results were obtained: The act of criminalizing a person using the ITE law instrument, which as previously explained is a concern for me as a writer for criminalization which is currently very common in Indonesia with various types of cases. Human rights that protect the right of every individual to express opinions and thoughts in public. His suggestion is the need for integrity from a judge who decides a case later so as not to make a wrong and unfair decision because he decides to punish someone who should be innocent but is found guilty. And the importance of awareness from law enforcement authorities is demanding someone who previously did not commit a crime but seems to have committed a criminal act or criminalized someone so that they have strong and professional integrity, always prioritize the legal interests and justice of the people or the majority above personal interests so that later cases like this not seen again in the future.